2004
DOI: 10.1007/s00170-003-2026-y
|View full text |Cite
|
Sign up to set email alerts
|

Time scale effects in laser material removal: a review

Abstract: In laser material removal using a continuous wave or long-pulsed laser, the primary material removal mechanism melts with molten metal often ejected by an assisting oxygen jet. Interactions between heat transfer, oxygen diffusion, and gas dynamics have been studied. In laser machining using a Q-switched solid state laser with pulse width on the order of nanoseconds, the primary material removal mechanism is ablation, but substantial melting is still present if a metallic material is concerned. Two mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 20 publications
1
37
0
5
Order By: Relevance
“…He has also shown that the variation in the power intensity results in considerable variation in the kerf size during the cutting, which is more pronounced at lower intensities. Zhang et al [5] have proposed a synthetic evaluation method for laser cutting quality. B S Yilbas et al [6] using a CO 2 laser with variable pulse frequency and Oxygen, as assisting gas, at different pressures have investigated the cutting process.…”
Section: ©Ijraset (Ugc Approved Journal): All Rights Are Reservedmentioning
confidence: 99%
“…He has also shown that the variation in the power intensity results in considerable variation in the kerf size during the cutting, which is more pronounced at lower intensities. Zhang et al [5] have proposed a synthetic evaluation method for laser cutting quality. B S Yilbas et al [6] using a CO 2 laser with variable pulse frequency and Oxygen, as assisting gas, at different pressures have investigated the cutting process.…”
Section: ©Ijraset (Ugc Approved Journal): All Rights Are Reservedmentioning
confidence: 99%
“…As shown in Fig. 7a, under the action of the focused laser beam, the molten material is removed immediately from the workpiece by assist gas, and a hole which diameter is larger than the diameter of focused beam is formed [21]. Figure 7b shows the movements of laser beam without load.…”
Section: Actual Efficiency Of the Laser Beammentioning
confidence: 99%
“…Previous studies regarding surface quality have mostly focused on the influence of the inherent properties of laser beams, such as pulse duration, pulse energy and wavelength [13][14][15]. However, laser processing conditions, especially the interactions and correlation between the machining parameters and the microstructural properties of the material, can also play an important role in laser ablation and, consequently, on the induced machining quality [16][17][18][19]. Hence, it is necessary to study and optimize the laser processing parameters in order to reduce the induced defects and to increase the integrity of the modified cemented carbide surfaces, especially for cases of repetitive, gradual ablation by laser beams at the same location.…”
Section: Introductionmentioning
confidence: 99%